2012
DOI: 10.1074/jbc.m111.286203
|View full text |Cite
|
Sign up to set email alerts
|

A Novel RhoA/ROCK-CPI-17-MEF2C Signaling Pathway Regulates Vascular Smooth Muscle Cell Gene Expression

Abstract: Background: MEF2C is essential for vascular smooth muscle development, yet the signaling pathways that regulate its function in this cell type remain largely unknown. Results: We identify a novel regulator of MEF2C in vascular smooth muscle, called CPI-17. Conclusion: Our data identify a genetic pathway involving CPI-17, MEF2C, and myocardin. Significance: These findings have important ramifications during vascular development and for stem cell programming.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 36 publications
3
58
0
Order By: Relevance
“…[23][24][25] Indeed, ROCK suppression via Y27632 almost completely reduced the phosphorylation of MyPT and MLC and, in parallel, reduced the protein levels of ␣-SMA regardless of VEGF-A stimulation in Flk1 ϩ MPCs ( Figure 3D; supplemental Figure 5A). Indeed, Y27632 reduced ␣-SMA ϩ MC population by ϳ 83% and MLC kinase inhibitor ML7 (5M) reduced ␣-SMA ϩ MC population by ϳ 31%, and combination of Y27632 and ML7 further reduced ␣-SMA ϩ MC population by ϳ 91% (Figure 3G-H).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[23][24][25] Indeed, ROCK suppression via Y27632 almost completely reduced the phosphorylation of MyPT and MLC and, in parallel, reduced the protein levels of ␣-SMA regardless of VEGF-A stimulation in Flk1 ϩ MPCs ( Figure 3D; supplemental Figure 5A). Indeed, Y27632 reduced ␣-SMA ϩ MC population by ϳ 83% and MLC kinase inhibitor ML7 (5M) reduced ␣-SMA ϩ MC population by ϳ 31%, and combination of Y27632 and ML7 further reduced ␣-SMA ϩ MC population by ϳ 91% (Figure 3G-H).…”
mentioning
confidence: 99%
“…[19][20][21] ROCK consists of 2 subtypes, ROCK1 and ROCK2, which both carry critical functions in the regulation of actin cytoskeleton assembly across many cell types through direct activation of myosin light chain and inactivation of myosin phosphatase. [19][20][21][22] ROCK also plays a key role in myogenic differentiation, [23][24][25] and recent studies have shown that Y27632 blocks the dissociation-induced apoptosis in human ESCs through suppression of Rho-ROCK pathway-mediated hyperactivation of actomyosin. [26][27][28] In the present study, we demonstrate how suppression of ROCK profoundly promotes the differentiation and expansion of ECs in our established feeder cell-free, 2-dimensional Matrigel system.…”
Section: Introductionmentioning
confidence: 99%
“…6K). Because ROCK1 and ROCK2 are known to affect myogenic gene expression (Castellani et al, 2006;Olson and Nordheim, 2010;Pagiatakis et al, 2012), we examined whether cadherin-11-mediated intercellular adhesion affected the expression of the key myogenic regulator, SRF. Indeed, the expression of SRF was significantly reduced both by treatment with Y27 and in siCDH11 cells (Fig.…”
Section: Cadherin-11 Regulated Smc Differentiation In Part Through Thmentioning
confidence: 99%
“…6C). As myogenic specific genes are transcriptionally activated by the SRF-MYOCD complex predominately and this mechanism was governed by the RhoA/ROCK signaling in the upstream [40][41][42], we treated the coculture environment with a specific RhoA/ROCK inhibitor, Y27632. The treatment with Y27632 did not obviously disturb the formation of cell aggregation structures, but suppressed the MYOCD elevation during coculture (Fig.…”
Section: Et Almentioning
confidence: 99%